Qualidade na prestação de serviços fisioterápicos - um estudo de caso sobre expectativas e percepções de clientes - Griebeler, Deizi (2006)
The present study approaches quality in the physiotherapy services rendered through the comparison between expectations and customers' perceptions. The study was developed in a Physiotherapy clinic from Santa Maria's city with Pilates praticant. SERVQUAL scale was used to evaluate the quality services. SERVQUAL scale makes possible a comparison between customers expectations about rendered services and their perceptions about the same. Eighty eight customers answered the questionnaire. SERVQUAL scale dates were submitted to Descriptive Statistics. In the twenty two total questions to the Scale we found twelve questions where the quality perception was higher than expectations. Three questions presented very much a like seemed average between the expectations and perceptions and in seven the expectations were higher than perceptions. Data were also submitted to Multivariate Exploratory Techniques, for the purpose to verify the presence or not of redundant subjects in the SERVQUAL scale adapted to Physiotherapy. Multivariate Exploratory Techniques allowed retreat redundant questions through exclusion criteria. Thereby, nine questions were eliminated to the questionnaire, result in a 8,828% decrease in the total variance among the original and the reduced version. This study made possible to detect improvement points in the services rendered by the clinic, furthermore it proposed an SERVQUAL scale with smaller number of questions without significant loss in its representation. In conclusions, other service section can take advantage in your research with the SERVQUAL driest version presented here.